PENENTUAN PRIORITAS PEMBANGUNAN JALAN DESA MENGGUNAKAN RURAL ACCESS INDEX (PRIORITY ASSESSMENT FOR RURAL ROAD DEVELOPMENT USING RURAL ACCESS INDEX) - Dimas Sigit Dewandaru (Jurnal Jalan-Jembatan, 2018)
Determining the priority of regional road development, especially rural roads, is still using methods objectively appro or by assessing field conditions. Programming of road construction carried out through the mechanism of RPJMDes and RKPDes has not provided a clear picture of the level of rural accessibility. Another method is Technical Guidelines (Juknis) for District Road Planning issued by the Directorate General of Highways. This technical guide generally contains a planning approach based on the calculation of priority scale based on the average daily traffic (LHR), and calculation of the cost-benefit value (Net Present Value (NPV / km). Both methods produce calculations that are more likely to prioritize roads that have a level conditions for severe road damage or high traffic, even though there are areas that need road construction related to the accessibility of the population, such as access to education, health, trade or agricultural centers.To determine whether a village has adequate accessibility of road infrastructure, it is necessary an analysis method that can produce a value (index) for accessibility, one of them is the rural accessibility assessment method issued by the World Bank, namely the Rural Access Index (RAI). RAI uses a calculation method that uses a fixed variable population to access a specific area. Low RAI value indicates that the area is need road access. This study compares the results of the use of three methods for prioritizing rural road development by taking case studies in the Ciwidey Agropolitan Area. The comparison of the three methods shows that the use of RAI is superior to its ability to provide an index (assessment) of the accessibility of rural roads to a specific area needed by the community, such as access to agricultural land in a case study that is associated with the proportion of the population passing through it. Keywords: rural road, road data assessment, priority program, accessibility, RAI.